Kekosongan Hukum Acara Dan Krisis Access To Justice Dalam Kasus-Kasus Pemberhentian Kepala Daerah/Wakil Kepala Daerah Di Indonesia - Azis, Arasy Pradana (UI Scholars Hub, 2023)
Law Number 23 Year 2014 on Regional Government (Law No. 23/2014) provides that the Regional Head or Deputy Regional Head may be dismissed in the middle of his term by certain reasons. The law also regulates a strict process, including the involment of the Supreme Court (MA) in it. MA provides a judicial test of the opinion of the Regional House of Representatives (DPRD) as the initiator of the dismissal processl. The involvement of the Supreme Court is a consequence of the strengthening of the legitimacy of the Head of Region/Deputy Head of Region, which is now elected directly by the people. Therefore, dismissal of Head of Region/Deputy Head of Region is designed difficult. However there is a problem of access to justice in the judicial process in MA, mainly due to the blur of procedural law. The concept of access to justice has been interpreted in a limited way, solely as access to legal assistance for the poor and marginalized.